1979
DOI: 10.1111/j.1469-7998.1979.tb03964.x
|View full text |Cite
|
Sign up to set email alerts
|

Allometry of the limb bones of mammals from shrews (Sorex) to elephant (Loxodonta)

Abstract: Measurements have been made of the principal leg bones of 37 species representing almost the full range of sizes of terrestrial mammals. The lengths of corresponding bones tend to be proportional to (body mass)0·35 and the diameters to (body mass)0·36, except in the family Bovidae in which the exponents for length are much nearer the value of 0·25 predicted by McMahon's (1973) theory of elastic similarity. Comparisons are made between mammals of similar size belonging to different orders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
175
0
16

Year Published

1997
1997
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 381 publications
(199 citation statements)
references
References 9 publications
8
175
0
16
Order By: Relevance
“…However, few have examined the epiphyses of those bones (i.e., near the joints), where muscle forces are transferred. For the humerus, it has been shown that the midshaft diameter and the humeral mass scale to body mass with scaling factors of 0.35 and 1.083, respectively [29,31,32]. These results indicate that the relationships between these values and body mass are nearly isometric; the geometry of the bone is maintained with increasing body size.…”
Section: Resultssupporting
confidence: 58%
See 1 more Smart Citation
“…However, few have examined the epiphyses of those bones (i.e., near the joints), where muscle forces are transferred. For the humerus, it has been shown that the midshaft diameter and the humeral mass scale to body mass with scaling factors of 0.35 and 1.083, respectively [29,31,32]. These results indicate that the relationships between these values and body mass are nearly isometric; the geometry of the bone is maintained with increasing body size.…”
Section: Resultssupporting
confidence: 58%
“…It also points to nearly geometric scaling between the humeral head and body mass. A number of studies have examined the relationships between bone geometry and animal body size [27][28][29][30]. However, few have examined the epiphyses of those bones (i.e., near the joints), where muscle forces are transferred.…”
Section: Resultsmentioning
confidence: 99%
“…(a) Body mass proxy data Femoral length was used as a body size proxy because it shows a consistent relationship with body mass in terrestrial vertebrates [33], and has been used in previous studies of archosauromorphs [31,32]. Femora have not been described for 77 per cent of the therapsids sampled, but use of femoral length was required to yield absolute values comparable with those of Archosauromorpha.…”
Section: Methodsmentioning
confidence: 99%
“…If nothing else this can serve as a reminder that even excellent agreement with the data need not imply any support for the theoretical curve that was fitted (Kooijman accordingly defends his formula on the basis of a priori arguments 41 ). In the example of mammalian long bones, bone dimensions have been linked to body mass via power laws, with various arguments in favour of different values for the exponents 61,62 ; it quickly became clear that different groups of mammals seem to have different best-fitting exponents 63 , and advanced models are based on specific details regarding the animal's stance 62 . The gains come at the cost of sacrificing what might be the main appeal of allometry, which is the idea that the posited power laws owe their universality to fundamental structural-mechanical constraints.…”
Section: Biomechanics On All Scales Of Lifementioning
confidence: 99%